Clinical guidance for diagnosis and management of suspected Pediatric Acute‐onset Neuropsychiatric Syndrome in the Nordic countries. (6th May 2021) - Pfeiffer, Helle Cecilie Viekilde; Wickstrom, Ronny; Skov, Liselotte; Sørensen, Camilla Birgitte; Sandvig, Inger; Gjone, Inger Helene; Ygberg, Sofia; de Visscher, Caroline; Idring Nordstrom, Selma; Herner, Linn Breen; Hesselmark, Eva; Hedderly, Tammy; et al.
Abstract: Pediatric acute‐onset neuropsychiatric syndrome is a clinical concept used to describe a subgroup of children with sudden onset of psychiatric and somatic symptoms. The diagnostic term and especially management of children differs depending on the clinical setting to which they present, and the diagnosis and management is controversial. The aim of this paper is to propose a clinical guidance including homogenous diagnostic work‐up and management of paediatric acute onset neuropsychiatric syndrome within the Nordic countries. The guidance is authored by a Nordic‐UK working group consisting of paediatric neurologist, child psychiatrists and psychologists from Denmark, Norway, Sweden and Great Britain, and is the result of broad consensus. Conclusion: Consensus was achieved in the collaboration on work‐up and treatment of patients with paediatric acute‐onset neuropsychiatric syndrome, which we hope will improve and homogenise patient care and enable future collaborative research in the field.